Cloning and Expression of Nonstructural Protein NS1 of Dengue Virus Serotype 2 - BETI ERNAWATI DEWI; FITHRIYAH FITHRIYAH; ANDRIANSJAH RUKMANA; PAISAL PAISAL; DEKA LARASATI; TJAHJANI MIRAWATI SUDIRO (Indonesian Society for microbiology, 2012)
Early diagnosis of dengue virus (DENV) infection is affirmative for patient management and control of the disease. Detection of nonstructural-1 (NS1) antigen has been proven to provide early detection of DENV infection. Commercial NS1 antigen assays are available in Indonesia with variable sensitivity. In an attempt to develop an NS1-based diagnostic test, we successfully cloned NS1 gene of DENV2 to a glutathione Stransferase- based vector pGEX6P-1 in Escherichia coli system. The recombinant protein (pG2NS12) was expressed in E. coli BL21. After induction with isopropyl-β-D-thiogalactoside 0.1 mM for 4 h at 25 °C a recombinant protein GST-NS1 with molecular size of approximately 75 kDa was obtained. The fusion protein was insoluble and found in the pellet fraction of the cell lysate. Addition of lysozyme (10 mg mL-1) and DNase-I (7.2 mg mL-1) in the lysis buffer was necessary to collect proteins from the pellet fraction. The proteins in the cell pellet were fractionated through Sephadex-G100 column, and GST-NS1 was further purified with Glutathione-Sepharose 4B beads. To obtain pure recombinant NS1 protein to be used in the immunization of mice, the fusion protein was cut with PreScission Protease® by addition of 0.075% Triton-X 100 was necessary to cut the fusion protein. We found that antibodies that recognized the recombinant NS1 protein and DENV2 virus were produced in mice immunized with purified NS1 protein. Therefore, our recombinant NS1 could be used to produce antibody that is potentially useful for developing diagnostic assay to determine the presence of dengue virus NS1 antigen in patient sera.